Protecting Against the Dead? On the Possible Use of Apotropaic Magic in the Oseberg Burial. Issue 1 (1st February 2016) - Bill, Jan
Abstract : The use of apotropaic practices, that is, of magic to protect against evil, is sometimes included in archaeological interpretations on the basis of similarities between archaeological objects and objects used in historically documented or present-day apotropaic practices. The present article attempts to develop the archaeological study of apotropaism by focussing on apotropaic ritual, in addition to apotropaic devices. The case study is a burial inad 834 of a high-ranking Viking Age woman in the Norwegian Oseberg ship grave. Drawing on cognitive magic ritual theory, the study focuses on identifying both a repeated ritual core and a counter-intuitive, magic element in the series of actions that led to the deposition of five elaborately carved wooden animal heads in the burial, each combined with a rattling device probably related to horse driving. The study demonstrates that apotropaism provides a viable explanation for this rather puzzling aspect of the burial. In a wider perspective it emphasizes the importance of the contextual, in addition to the functional, interpretation of objects in graves. It also suggests that the use of animal figures and animal style in Viking Age artwork may have been more intimately connected with apotropaic beliefs than previously suggested.